An innovative approach based on meta-learning for real-time modal fault diagnosis with small sample learning - Lei, Tongfei; Hu, Jiabei; Riaz, Saleem (Frontiers in Physics, 2023)
The actual multimodal process data usually exhibit nonlinear time correlation, non-Gaussian distribution accompanied by new modes, etc. Existing fault diagnosis methods have difficulty adapting to the complex nature of new modalities and are unable to train models based on small samples. Therefore, this paper proposes a new modal fault diagnosis method based on me-ta-learning (ML) and neural architecture search (NAS), MetaNAS. Specifically, the best per-forming network model of the existing modal is first automatically obtained using NAS, and then the fault diagnosis model design is learned from the NAS of the existing model using ML. Finally, when generating new modalities, the gradient is updated based on the learned design experience, i.e., new modal fault diagnosis models are quickly generated under small sample conditions. The effectiveness and feasibility of the proposed method are fully verified by numerical system and simulation experiments of Tennessee Eastman (TE) chemical process. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership. References should not be cited in the abstract. Leave the Abstract empty if your article does not require oneplease see the "Article types" on every Frontiers journal page for full details.